SweParaphrase - Språkbanken Text (University of Gothenburg, 2024)
A subset of the Semantic Textual Similarity reference data (STS Benchmark).

En delmängd av referensdatan för semantisk textjämförelse (STS Benchmark).
SveParafras
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik